STRATEGIES TO PREVENT THE SMUGGLING OF ILLEGAL COMMUNICATION DEVICES THROUGH OFFICER DISCIPLINE AT THE WOMEN'S CORRECTIONAL INSTITUTION CLASS IIA JAKARTA - Jati, Azzah Al Maroro; Soge, Markus Marselinus (Universitas Nusa Cendana, 2025)
This research focuses on strategies to prevent the smuggling of illegal communication devices through officer discipline at the Women's Correctional Institution Class IIA Jakarta. The background highlights the rising concerns about security and order within correctional facilities due to the illicit use of communication devices by inmates. The study aims to identify effective disciplinary measures and operational protocols that can enhance compliance among officers and inmates. Employing a qualitative research method, data were collected through observations, document analysis, and informal interviews to explore the implementation of preventive strategies. The findings indicate that the institution's strategies include socialization of regulations, strict sanctions for violations, regular inspections, and the promotion of a strong work culture among officers. Despite these efforts, challenges such as inconsistent supervision and low motivation among staff were noted, suggesting the need for continuous improvement in monitoring and staff engagement to enhance the overall effectiveness of the prevention strategies. Keywords: Smuggling Prevention; Officer Discipline; Correctional Institution